2015
DOI: 10.1371/journal.pone.0136092
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Sentiment on Twitter: An Unsolicited Public Opinion Poll

Abstract: The consequences of anthropogenic climate change are extensively debated through scientific papers, newspaper articles, and blogs. Newspaper articles may lack accuracy, while the severity of findings in scientific papers may be too opaque for the public to understand. Social media, however, is a forum where individuals of diverse backgrounds can share their thoughts and opinions. As consumption shifts from old media to new, Twitter has become a valuable resource for analyzing current events and headline news. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
161
3
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 227 publications
(195 citation statements)
references
References 27 publications
6
161
3
8
Order By: Relevance
“…The labMT, LIWC 2007, and ANEW unigram sentiment instruments were used to quantify the happiness of tweet language (3639). The use of labMT, which has shown strong prior performance in analyzing happiness on Twitter (40,41), is novel with respect to depression screening; ANEW and LIWC have been successfully applied in previous studies on depression and Twitter (7,8,14). LIWC was also used to compile frequency counts of various parts of speech (e.g., pronouns, verbs, adjectives) and semantic categories (e.g., food words, familial terms, profanity) as additional predictors (36).…”
Section: Feature Extractionmentioning
confidence: 99%
“…The labMT, LIWC 2007, and ANEW unigram sentiment instruments were used to quantify the happiness of tweet language (3639). The use of labMT, which has shown strong prior performance in analyzing happiness on Twitter (40,41), is novel with respect to depression screening; ANEW and LIWC have been successfully applied in previous studies on depression and Twitter (7,8,14). LIWC was also used to compile frequency counts of various parts of speech (e.g., pronouns, verbs, adjectives) and semantic categories (e.g., food words, familial terms, profanity) as additional predictors (36).…”
Section: Feature Extractionmentioning
confidence: 99%
“…For example, current studies infer network influence from self-reported survey data (Brody et al, 2008;Leombruni, 2015) rather than analyzing and constructing actual social networks. Yet, with the increasing spread and transmission of risk information on social media, new theories and methods are being developed, including "social contagion theories of risk" (Scherer & Cho, 2003), social tipping points (Kinzig et al, 2013; van der Linden, 2017), "sentiment" analyses on Twitter (Cody et al, 2015), and the role of network opinion leaders (Nisbet & Kotcher, 2009). In short, much exciting research remains to be done on the topic of normative influence and its impact on concern about global warming.…”
Section: Social and Cultural Influences The Social Construction Of Riskmentioning
confidence: 99%
“…Kirilenko and Stepchenkova [2] used a 1-million sample of tweets to research geographical variations in climate change discourse worldwide. Cody et al [3] analyzed 1.5 million tweets containing the words "climate" to explore temporal changes in sentiment (described in the paper as "a tool to measure happiness") expressed by the people in relation to climate change. Yang et al [4] researched the effect of climate and seasonality on depressed mood using automated content analysis of 600 million tweets.…”
Section: Introductionmentioning
confidence: 99%